2022
DOI: 10.3389/fcimb.2022.827129
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Traditional Chinese Medicine Improves Functional Outcome in Acute Ischemic Stroke: From Clinic to Mechanism Exploration With Gut Microbiota

Abstract: As a life-threatening disease, stroke is the leading cause of death and also induces adult disability worldwide. To investigate the efficacy of the integrated traditional Chinese medicine (ITCM) on the therapeutic effects of acute ischemic stroke (AIS) patients, we enrolled 26 patients in the ITCM [Tanhuo decoction (THD) + Western medicine (WM)] group and 23 in the WM group. Thirty healthy people were also included in the healthy control (HC) group. ITCM achieved better functional outcomes than WM, including s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 38 publications
3
17
0
Order By: Relevance
“…[ 34 ] Moreover, the genus Dorea was inversely correlated to atherosclerosis in mice [ 35 ] and the concentration of trimethylamine N‐oxide [TMAO] in acute ischemic stroke patients. [ 36 ] However, Erysipelotrichaceae at the family level were potentially pathogenic bacteria because its some specific taxa were correlated to dyslipidemia [ 37 ] and inflammation. [ 38 ] Therefore, in line with the majority of previous studies, our findings supported that 25(OH)D has the potential to lower the progression of subclinical atherosclerosis via modulating the gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…[ 34 ] Moreover, the genus Dorea was inversely correlated to atherosclerosis in mice [ 35 ] and the concentration of trimethylamine N‐oxide [TMAO] in acute ischemic stroke patients. [ 36 ] However, Erysipelotrichaceae at the family level were potentially pathogenic bacteria because its some specific taxa were correlated to dyslipidemia [ 37 ] and inflammation. [ 38 ] Therefore, in line with the majority of previous studies, our findings supported that 25(OH)D has the potential to lower the progression of subclinical atherosclerosis via modulating the gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Chinese herbs maintain a healthy gut environment by promoting bowel movement and stimulating bowel movements. For example, Xinglou Chengqi Decoction (XCD) and Tanhuo decoction (THD) are both effective in improving gut dysfunction caused by AIS, reducing symptoms such as bad breath, thick tongue, bloating, dry stools or poor bowel movements ( Chen et al, 2020 ; Wang et al, 2021 ; Guo et al, 2022 ). The gut motility-promoting effect of Chinese herbs may be related to their stimulation of the release of intestinal neurotransmitters.…”
Section: Tcm Treats Ais By Interacting With the Gut Microbiotamentioning
confidence: 99%
“…Several studies have found that Chinese herbs can upregulate SCFA levels to improve the prognosis of AIS by correcting disorders of the gut microbiota. THD makes SCFA-producing flora such as Blautia, Coprococcus, Streptococcus, Dorea, Streptococcus, Bifidobacterium, and Lactobacillus more accessible to healthy people ( Guo et al, 2022 ). XCD can upregulate Verrucomicrobia and Akkermansia abundance to increase the levels of enteric butyric acid ( Gao et al, 2021 ).…”
Section: Tcm Treats Ais By Interacting With the Gut Microbiotamentioning
confidence: 99%
See 1 more Smart Citation
“…Stimulation of specific acupoints along the collaterals may help control the meridian qi (or vital energy), dredge the meridians, and restore the body Yin-Yang balance. [9,10] Jin three needles, a characteristic acupuncture therapy in the Lingnan area, is widely used in clinical practice, particularly for encephalopathy. [11] The pathogenesis of stroke is considered to be an imbalance of Yin and Yang, inversion of Qi and blood, and obstruction of the viscera and qi.…”
Section: Introductionmentioning
confidence: 99%